The Metaphysics of Pan-Islamism: A Philosophical Deconstruction of Iranian ‘Irfān-i Siyāsī and the Epistemic Veil of Indonesian Moderation - Rahmad Hidayat; Hendrawangsyah Hendrawangsyah; Mahsur Mahsur (Sekolah Tinggi Agama Islam Sadra, 2026)
This article deconstructs the contemporary crisis of Pan-Islamism, which has undergone a desacralization from the metaphysical essence of unity (waḥdah) into a pragmatic instrument of the nation-state. The research objective is to re-evaluate the spiritual foundation of Islamic political solidarity amidst global secular hegemony. Utilizing the framework of theopolitics of the absolute and neo-Sufism, this study performs a comparative-ontological analysis of two polar orientations: Iran’s ontology of resistance and Indonesia’s epistemology of moderation. This study asserts that Indonesia represents a desacralization crisis, where its moderation model acts as an epistemic hijab that reduces Islam’s transcendental energy into sociological harmony compromised by Western-liberal narratives. This decline is analyzed through the malady of al-wahn—excessive love for materiality—which erodes the ummah’s ontological courage. Conversely, Iran actualizes irfān-i siyāsī, a transformative mysticism grounded in waḥdah al-wujūd and futuwwah, integrating tazkiyah al-nafs with revolutionary struggle. The primary finding affirms that authentic Pan-Islamism is a logical consequence of theological negation (lā ilāha), suggesting that true Sufism is not an escapist retreat but zuhud-activism—a manifesto of liberation against modern idols of power. This spirit resonates with Malāmatiyyah-anarchism, a chivalrous courage (al-fatā) to resist structural injustice. The conclusion offers a re-orientation of Pan-Islamism rooted in ontological sovereignty, restoring politics as a sacred stage for Divine justice through a fusion of inner depth and concrete socio-political action.